Persepsi Warga Negara Indonesia EKS Timor Leste Terhadap Stigma Sosial di Kabupaten Belu - Kefi, Adrianus Rano; Wijaya, R. Pasifikus Ch.; Panis, Marleny P.; Lerik, M. Dinah Ch. (Jurnal Inovasi Global, 2025)
Conflict is a situation when two or more parties try to hinder each other's achievement of their goals due to differences in opinions, values, and demands. The history of political and social conflicts experienced by East Timor until it became the state of Timor Leste has left a lasting social impact, especially for Indonesian citizens (WNI) who are former Timor Leste refugees. One of these impacts is in the form of the emergence of negative stigma in the local community. This study aims to find out and understand the form of stigma experienced by ex-Timorese citizens and the social factors behind it. The research method used is a qualitative approach with a descriptive design. The participants in this study are five ex-Timorese citizens who are domiciled in Belu Regency. The data collection technique was carried out through in-depth interviews to explore the subjective experiences of participants related to their social interactions with the local community. The results of the study show that ex-Timorese citizens still often receive negative labeling from local residents, such as being considered different, less trusted, and associated with past conflicts. This stigma affects the social life of participants, including in terms of social acceptance, relationships between citizens, and a sense of security in the community. This study confirms that negative stigma arises due to differences in social identity and post-conflict social construction. Therefore, social education efforts and strengthening community integration are needed to reduce stigma and encourage more inclusive social cohesion.